The Faculty of Computing building will be operational next October - Nor Salwana, Mohammad Idris (2020)
Pekan, 9 September 2020 - The Faculty of Computing (FK) building, Universiti Malaysia Pahang (UMP) in Pekan will be fully operational soon when it is officially handed over by the Public Works Department of Malaysia (JKR) to the university in a ceremony held at the Lecture Hall, FK recently.